Chitinases of Bacillus thuringiensis: Phylogeny, Modular Structure, and Applied Potentials - Martínez-Zavala, Sheila A.; Barboza-Pérez, Uriel E.; Hernández-Guzmán, Gustavo; Bideshi, Dennis K.; Barboza-Corona, José E. (Frontiers in Microbiology, 2020)
The most important bioinsecticide used worldwide is Bacillus thuringiensis and its hallmark is a rich variety of insecticidal Cry protein, many of which have been genetically engineered for expression in transgenic crops. Over the past 20 years, the discovery of other insecticidal proteins and metabolites synthesized by B. thuringiensis, including chitinases, antimicrobial peptides, vegetative insecticidal proteins, and siderophores, has expanded the applied value of this bacterium for use as an antibacterial, fungicidal, and nematicidal resource. These properties allow us to view B. thuringiensis not only as an entity for the production of a particular metabolite, but also as a multifaceted microbial factory. In particular, chitinases of B. thuringiensis are secreted enzymes that hydrolyze chitin, an abundant molecule in the biosphere, second only to cellulose. The observation that chitinases increase the insecticidal activity of Cry proteins has stimulated further study of these enzymes produced by B. thuringiensis. Here, we provide a review of a subset of our knowledge of B. thuringiensis chitinases as it relates to their phylogenetic relationships, regulation of expression, biotechnological potential for controlling entomopathogens, fungi, and nematodes, and their use in generating chitin-derived oligosaccharides that possess antibacterial activities against a number of clinically significant bacterial pathogens. Recent advances in the structural organization of these enzymes are also discussed, as are our perspective for future studies.